If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 36 = 112 Reorder the terms: 36 + c = 112 Solving 36 + c = 112 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + c = 112 + -36 Combine like terms: 36 + -36 = 0 0 + c = 112 + -36 c = 112 + -36 Combine like terms: 112 + -36 = 76 c = 76 Simplifying c = 76
| 10x+3(3x-7)=-2 | | 5w=-27.5 | | 8x-6=74whatisx | | -13-21p=8 | | -7r-16=-3r-8r | | 2x-(5-x)-7=x-4x | | 3y-xy=-4x-9 | | 3(x-2)=5x-3 | | 6-4x=7x-9-8 | | 5x^2+25x+30=-5x^2 | | 3x(-12)-6=4x | | 4+1-3m-3m=-2m-3m | | 1.2(7.2-0.3x)=-4.1x | | 4x-3(-2x+5)=40 | | 2x^2+3x-24=0 | | x^2-24x+50=-8x+2 | | x+2x+(x-12)=180 | | -(8y+2)-(7y-5)=-1 | | 9-1/2(3n-6)=n+2 | | 20n+4=24n-40 | | 2b+4=9+3b | | 5(x-2)=10(2-x) | | 0=z^2-(1+2i)z-x+2i | | 1+6x+3=5x+2 | | 0.5x^2-6=x^2+4x | | 4x+8+3x+9=13 | | f=-9+16 | | 15-8*2+12= | | -7p-4=-2p-14 | | 2[4-2(3-x)]-1=4[2(x-3)+7]-25 | | 99-4b=-11b | | 1+1+7a+3=a-1+4a |